Effect of Dao Jiang Ping (DJP) Model Based Module on Learning Result of XI Class Students - Suciati Suciati; Maridi Maridi; Nurul Kusuma Dewi; Dedy Subandowo; Anggit Sasmito (Yayasan Keluarga Guru Mandiri, 2020)
Learning outcomes are an evaluation mechanism in the curriculum to achieve graduates competency standards. Student learning outcomes include cognitive, affective, and psychomotor aspects. The purpose of this research is to know the effect of DJP Model based module to student learning result of class XI. The research used experimental method with pretest-posttest control group design. The research population is all of the XI MIA class of SMA Negeri 1 Geger with a total number of 192 students scattered into six classes. The sample which is taken by using simple random sampling technique resulted in two classes, namely XI MIA 3 class (experimental class using DJP Model module) which consist of 34 students and XI MIA 6 (control class using teaching material in school) which consist of 34 students. Data collection techniques are done through test (measuring cognitive learning outcomes) and non-tests (measuring affective and psychomotor learning outcomes). The research instruments used in this research were multiple choice questions, observation sheets, and documentation. The data were analyzed using SPSS 18 t-test with significance level of 0.05. The result of the analysis showed the experimental cognitive learning result of experimental class is higher (75,29 with 76,47% completeness) than control class (59,12 with 8,82% completeness) with significance level 0,000. The affective learning outcomes of experimental class were higher (89.78) than the control class (23.43) with significance level of 0.000. The experimental psychomotor learning outcomes of experimental class were higher (90.72) than control class (9,84) with a significance level of 0.000. Based on the results of the research can be concluded that the DJP Model-based Module gives positive effect on student learning outcomes of XI graders.